2016
DOI: 10.1002/2015jg003162
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on nitrogen cycling and nitrate removal‐production efficiency in bed form‐induced hyporheic zones

Abstract: Hyporheic flow in aquatic sediment controls solute and heat transport thereby mediating the fate of nutrients and contaminants, dissolved oxygen, and temperature in the hyporheic zone (HZ). We conducted a series of numerical simulations of hyporheic processes within a dune with different uniform temperatures, coupling turbulent open channel fluid flow, porous fluid flow, and reactive solute transport to study the temperature dependence of nitrogen source/sink functionality and its efficiency. Two cases were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 54 publications
7
77
0
Order By: Relevance
“…Temperature is another driver of biogeochemical transformation rates [ Zheng, et al ., 2016], providing another potential cause of the observed perturbation. However the temperatures recorded at the monitoring points, while correlated with changes in gradient, only varied by about 2°C over the study period, implying that temperature variations within the subsurface, and the corresponding reaction rate variations that would follow, are not the primary drivers of biogeochemical perturbation at this study site.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature is another driver of biogeochemical transformation rates [ Zheng, et al ., 2016], providing another potential cause of the observed perturbation. However the temperatures recorded at the monitoring points, while correlated with changes in gradient, only varied by about 2°C over the study period, implying that temperature variations within the subsurface, and the corresponding reaction rate variations that would follow, are not the primary drivers of biogeochemical perturbation at this study site.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, denitrification is of great importance because it enables the permanent removal of nitrogen from the aquatic system (Harvey & Bencala, ; Zarnetske et al, ). Whether the hyporheic zones acts as a nitrate source or sink also depends strongly on the ratio between the in‐stream concentrations of ammonium and nitrate (Marzadri et al, ; Zheng et al, ). In general, hyporheic exchange flows have a crucial impact on the health of our riparian ecosystems by increasing solute residence times and thus solute exposure to microbial communities, which in turn fosters biogeochemical cycling of nutrients and contaminants (Battin et al, ; Mulholland et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed process‐based numerical models were developed at the scale of single geomorphological structures, also coupled with heat and solute transport, including multiple reacting and interacting species (e.g., Marzadri et al, ; Zheng et al, ). These models allow for a holistic investigation of exchange and transformation processes in the hyporheic zone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reactive transport modelling of the HB site, which ignored temperature effects, confirms the importance of the flood‐induced exchange on reactions occurring within the bank (Shuai et al, ). Modelling by Zheng, Cardenas, and Wang () showed that temperature influences the depth of nitrification and denitrification reactions and whether the HZ in streambeds was acting as a net source or sink of nitrate. The study showed that even 5 °C changes in temperature, under relatively nutrient‐ and carbon‐rich conditions (just like at our sites) and with all other physico‐chemical factors remaining the same, could lead to ~50–100% changes in reaction rates.…”
Section: Discussionmentioning
confidence: 99%